Facilitating exploratory talk through mathematical programming problems - Munthe, Morten (NOMAD Nordic Studies in Mathematics Education, 2024)
With several Nordic countries implementing programming into their curricula, there is a need for research into the combination of mathematical learning and programming. With tasks being the main ”thing to do” in the mathematics classroom and exploratory talk being closely linked to learning this article investigates what contri-butes to and what hinders exploratory talk when working on mathematical programming problems. The data collection comprises of recordings of students working on tasks in a mathematics classroom in Norway. The findings indicate that programming can facilitate mathematical talk in the classroom, that programming is best implemented to facilitate in-depth learning, and that adversities are present in both instances.